Corseul (Côtes-d’Armor), un quartier de la ville antique - Kerébel, Hervé (Éditions de la Maison des sciences de l’homme, 2023)
Under the direction of H. Kértbel, excavation on the site of Fanum Martis. present-day Corseul, has gradually revealed a vast trading and crafts centre within the archaeological protection area of Monterfil II. Uncovering a surface area of over 5000 m2 along the major axis of the former Coriosolati capital has enabled archaeologists to discern architectural and topographical changes which took place in this quarter from 15/10 BCE to the 4th century CE. The finds, which include a high proportion of Italian potters’ marks and Lipari amphorae, attest to the significance ot the town as a marketplace for items produced throughout the Mediterranean Basin. A metrological analysis of the remains, earned out by an archaeologist trained in architecture, has served as the basis for a reconstruction of elevations governed by the Tuscan order. Although there is still much work to be done in Corseul. the excavation carried out thus far at Monterfil II has shown how the urban layout and public and private domains were established during the reign of Augustus.